Kredytowanie budownictwa indywidualnego na wsi - Mikołajczak, Ryszard (Wydział Prawa i Administracji UAM, 1985)
The subject of the article is a bank credit given by cooperative banks for the development of individual housing for farmers. The author is trying to point out the possibility of taking into consideration, in the issue of the credit conditions delineated by the bank, not only economic criteria, connected to this economic category, but also of social criteria, which in turn are connected to the subject of crediting. The proposals to introduce changes into the system of crediting individual housing, changes taking into account economic and social aspects, would reach their expected goals more effectively. This would require, though, — according to the author, the introduction of several changes into the bank and credit system, pertaining to, among others, a growth of the autonomy of banking institutions and, as a result, the treatment of bank credit as an elastic source of finances for investment, and the growth of the bank's role in investment proceedings.
Credits for Individual Housing Enterprises in the Country